Cladistic analysis of Neocoelidiinae (Hemiptera: Cicadellidae) with description of a new tribe - Marques-Costa, Ana Paula; Cavichioli, Rodney Ramiro (Zootaxa, 2012)
A cladistic analysis of Neocoelidiinae was conducted, including representatives of 31 genera of the 32 comprised in the subfamily (except Krocarites Dietrich & Vega, known from a single fossil species) to obtain a hypothesis of relationships among them. The analysis was based on a matrix with 71 terminal taxa, and 85 characters of external morphology and male genitalia. It yielded a single most parsimonious tree, in which Neocoelidiinae appears as a monophyletic group. All the genera constitute natural groups, except Coelidiana Oman, which appears as polyphyletic. Krocodona Kramer, Krocozzota Kramer, Retrolidia Dietrich, and Krocolidia Dietrich, constituted a distinct clade in Neocoelidiinae, and for this reason, herein a new tribe, Krocodonini, is established in the subfamily to include these taxa.